Trends in Gender-based Health Inequality in a Transitional Society: A Historical Analysis of South Korea - Chun, Heeran (The Korean Society for Preventive Medicine, 2012)
OBJECTIVES: This study examined the trends in gender disparity in the self-rated health of people aged 25 to 64 in South Korea, a rapidly changing society, with specific attention to socio-structural inequality. METHODS: Representative sample data were obtained from six successive, nationwide Social Statistics Surveys of the Korean National Statistical Office performed during 1992 to 2010. RESULTS: The results showed a convergent trend in poor self-rated health between genders since 1992, with a sharper decline in gender disparity observed in younger adults (aged 25 to 44) than in older adults (aged 45 to 64). The diminishing gender gap seemed to be attributable to an increase in women's educational attainment levels and to their higher status in the labor market. CONCLUSIONS: The study indicated the importance of equitable social opportunities for both genders for understanding the historical trends in the gender gap in the self-reported health data from South Korea.